Antimicrobial Activity and Identification of the Biosynthetic Gene Cluster of X-14952B From Streptomyces sp. 135 - Li, Na; Chen, Simin; Yan, Zhiqiang; Han, Jinhua; Ta, Yongquan; Pu, Taixun; Wang, Yonghong (Frontiers in Microbiology, 2021)
The bacterial genus Streptomyces is an important source of antibiotics, and genome mining is a valuable tool to explore the potential of microbial biosynthesis in members of this genus. This study reports an actinomycete strain 135, which was isolated from Qinghai-Tibet Plateau in China and displayed broad antimicrobial activity. The fermentation broth of strain 135 displayed strong antifungal activity (>70%) against Sclerotinia sclerotiorum, Botrytis cinerea, Valsa mali, Phytophthora capsici, Glomerella cingulata, Magnaporthe grisea, Bipolaris maydis, Exserohilum turcicum in vitro, meanwhile possessed significant preventive and curative efficacy against Sclerotinia sclerotiorum, Gaeumannomyces graminis and Phytophthora capsici on rape leaves (54.04%, 74.18%), wheat (90.66%, 67.99%) and pepper plants(79.33%, 66.67%). X-14952B showed the greatest antifungal activity against Sclerotinia sclerotiorum and Fusarium graminearum which the 50% inhibition concentration (EC50) were up to 0.049 μg/mL and 0.04 μg/mL, respectively. Characterization of strain 135 using a polyphasic approach revealed that the strain displayed typical features of the genus Streptomyces. 16S rRNA gene sequencing and phylogenetic analysis demonstrated that the isolate was most closely related to and formed a clade with Streptomyces huasconensis HST28T (98.96% 16S rRNA gene sequence similarity). Average nucleotide identity (ANI) and DNA-DNA hybridization (DDH) values in strain 135 and related type strains were both below the threshold of species determination (91.39% and 56.5%, respectively). OrthoANI values between strain 135 and related type strains are under the cutoff of determining species (<95%). The biosynthetic gene cluster (BGC) designated to X-14952B biosynthesis was identified through genome mining and the possible biosynthesis process was deduced.